Pengaruh Pertumbuhan dan Hasil Tanaman Kedelai (Glycine max L. Merill) Di Bawah Tegakan Hutan Tanaman - Mulky Tamrin; Ramli Hadun; Suryati Tjokrodiningrat (Universitas Khairun, 2022)
Demand for soybeans is the main source of protein and vegetable oil which continues to increase, so the government's efforts continue to develop several superior soybean varieties and use of under-standing land which is influenced by light intensity. The purpose of this study was to determine the land suitability class and the effect of growth and yield of soybean under 10 year old Samama and Binuang plantations. This research used a factorial randomized block design (RAK) where Factorial A (variety), where (A1 = DENA 1, A2 = Anjasmoro) and Factor B (Stand), (B0 = open land, B1 = Binuang, B2 = Samama). Based on the results of the analysis of soil samples in the three stands, both Binuang, Samama and Open Land, it shows that the land suitability class is quite good (S2) for soybean cultivation, but there are still inhibiting factors in the form of temperature regime (t) and availability. water (w). Meanwhile, the growth of soybean plants showed a faster increase in height in Samama stands, compared to under Binuang stands and open land. The Least Significant Difference Test (LSD) at 5% showed that the Samama stand had a significantly different effect from Binuang stands and open land at the beginning of its growth, namely 7 DAS, 14 DAS, and 21 DAS. The number of leaves showed that there was no significant interaction effect between the variety (A) and the type of stand (B). From the results of the LSD test at 5% level, single factor treatment gave a significant difference on the number of leaves of soybean plants aged 14, 21, 28, 35, and 42 DAS.Keywords: Land suitability, growth and yield of soybean plants, under plantation forest stands